KEWENANGAN PEMERINTAH DAERAH DALAM DUKUNGAN PENGEMBALIAN PINJAMAN KOPERASI DESA MERAH PUTIH BERDASARKAN PERATURAN MENTERI DESA NOMOR 10 TAHUN 2025 - Nur Farida,; Tahegga Primananda Alfath, (Journal of Innovation Research and Knowledge, 2026)
In order to accelerate economic development, the Central Government launched a strategic initiative in the form of establishing Koperasi Desa Merah Putih (KDMP). To facilitate the KDMP's access to large amounts of capital from banks (State-Owned Banks Association/Himbara), the Government issued a supporting regulation, namely Permendes PDT 10/2025, which specifically regulates the Loan Repayment Support mechanism that must be provided by the Village Government. The purpose of this study is to examine the principles of appropriateness and priority in the use of village funds as regulated in the Village Law and the form and limits of the authority of Local Governments (Regencies/Cities) in drafting derivative regulations aimed at mitigating the fiscal and governance risks of KDMP. The research method used is a normative juridical method with a statutory approach and a conceptual approach. The study concluded that the allocation of funds to support loan repayments is appropriate as long as it functions as a safety net (not an initial guarantee) and is subject to a maximum limit of 30% of the annual village fund ceiling. The authority of local governments (regencies/cities) in drafting derivative regulations (regency/city regulations) has strict substantive limitations